COVID-19-RELATED ARTERIAL THROMBOSIS - O. NEMATZODA; A.D. GAIBOV; E.L. KALMYKOV; A.K. BARATOV (Avicenna Tajik State Medical University, 2021)
Objective: To study of the features of the course, diagnosis and treatment of acute arterial thrombosis in patients who have undergone or are suffering from COVID-19. Methods: A search was carried out for research papers published in the PubMed database before February 12, 2021, devoted to various aspects of the COVID-19-related lesions of the arterial system. Search keywords were: arterial thrombosis, COVID-19, SARS-CoV-2, endothelial dysfunction. In total, 373 articles were found in this database on the combination of COVID-19 and thrombotic complications (including arterial and venous). Among them (after excluding venous thrombosis), 54 corresponded to the specified search parameters and were analyzed in the following areas: the incidence of acute peripheral arterial thrombosis in COVID-19, the mechanisms of hemocoagulation changes depending on the effect of coronavirus infection, and modern principles of treatment. Results: The analysis of literature data has shown that acute arterial obstruction (AOA) rate occurs from 0.39% to 11.1%. According to most studies, the main risk factors for the development of AOA were the male gender, old age and comorbidity. The use of invasive imaging methods for diagnosis of acute arterial thrombosis is limited both due to the severity of the patient's status, the impossibility of transporting them, and the risk of infection spreading in relatively «safe» areas of other medical facilities. The authors adhere to different approaches, which sometimes do not correspond with the accepted standards and consensus for the treatment of AOA in «non-COVID» patients. However, all researchers agree on the importance and effectiveness of therapeutic anticoagulation and antiplatelet therapy for the arterial thrombosis in COVID-19 patients. Conclusion: Currently, many aspects of COVID-19-related arterial thrombosis require further study. COVID-19 pandemic has caused enormous damage to all areas of medicine, including the vascular surgery service, causing a decrease in the number of planned vascular operations. COVID-19-related arterial thrombosis is characterized by the enormous effort required to improve treatment outcomes and increase patient survival. Anticoagulation and antiplatelet therapy is the most effective method for both prevention and treatment of patients with arterial thrombosis associated with coronavirus infection.